MODEL PERAMALAN TIME SERIES PREDIKSI MINAT MAHASISWA MENGGUNAKAN DOUBLE EXPONENTIAL SMOOTHING - Samuel Carlos A. Manalu; Siti Aisyah; Livia Grace Malau; Clara Sinta Uly Manurung; Steven Hikari Hoshi Situngkir; Frainskoy Rio Naibaho; Raja Tama Andri Agus; Amalia Amalia; Muhammad Radhi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract : Changes in prospective students interest in majors university occur dynamically over time, requiring a forecasting method capable of accurately predicting interest trends. This study aims to apply the Double Exponential Smoothing (DES) method to predict the number of prospective students. The research employs a quantitative descriptive-analytical approach using secondary data on student interest from 2023 to 2025. The forecasting process is conducted using smoothing parameters for level (α) and trend (β), both set at 0.9. Furthermore, the accuracy of the forecasting model is evaluated using Mean Absolute Deviation (MAD), Mean Squared Error (MSE), and Mean Absolute Percentage Error (MAPE). The results indicate that the Double Exponential Smoothing method is effective in capturing the downward trend in student interest. The forecasted number of prospective students for 2026 is estimated at 462 students. Accuracy evaluation yields a MAD value of 98, an MSE of 19,208, and a MAPE of 18.63%, indicating that the forecasting error remains within an acceptable range. Therefore, the results of this study can be used as a supporting basis for strategic decision-making in planning new student admissions, strengthening promotional strategies, and managing academic resources. Keywords: forecasting time series, Double Exponential Smoothing, prediction, Student. Abstrak: Perubahan minat calon mahasiswa terhadap jurusan di perguruan tinggi terjadi secara dinamis dari waktu ke waktu, sehingga diperlukan metode peramalan yang mampu memprediksi tren peminatan secara akurat. Penelitian ini bertujuan menerapkan metode Double Exponential Smoothing (DES) dalam memprediksi jumlah minat mahasiswa. Metode penelitian yang digunakan adalah pendekatan kuantitatif deskriptif analitis dengan memanfaatkan data sekunder berupa jumlah minat mahasiswa pada tahun 2023–2025. Proses peramalan dilakukan dengan menggunakan parameter pemulusan level (α) dan tren (β) sebesar 0,9. Selanjutnya, tingkat akurasi model dievaluasi menggunakan ukuran kesalahan Mean Absolute Deviation (MAD), Mean Squared Error (MSE), dan Mean Absolute Percentage Error (MAPE). Hasil penelitian menunjukkan bahwa metode Double Exponential Smoothing dapat menangkap pola tren penurunan jumlah minat mahasiswa secara efektif. Nilai peramalan jumlah peminat pada tahun 2026 diperkirakan sebesar 462 orang. Evaluasi akurasi menghasilkan nilai MAD sebesar 98, MSE sebesar 19.208, dan MAPE sebesar 18,63%, yang menunjukkan bahwa tingkat kesalahan peramalan masih berada dalam batas yang dapat diterima. Dengan demikian, hasil penelitian ini dapat dijadikan sebagai salah satu dasar pendukung dalam pengambilan keputusan strategis terkait perencanaan penerimaan mahasiswa baru, penguatan promosi, serta pengelolaan sumber daya akademik. Kata Kunci: forecasting time series, Double Exponential Smoothing, prediksi,Mahasiswa